Primary Anorectal Melanoma-Uncommon Entity and Rare Presentation - Malhotra, Parveen; Malhotra, Naveen; Malhotra, Vani; Chugh, Ajay; Dahiya, Abhisekh Hemant (Journal of Hematology Research, 2014)
Background: Malignant melanomas of the gastrointestinal (GI) tract are usually metastatic. Primary malignant melanoma of the GI tract is rare and occurs mainly in the anorectum and esophagus, but can also involve stomach rarely. Case: We report a case of 65-year-old female who presented with short duration of anemia but on detailed evaluation had primary Anorectal melanoma (ARM) with extensive metastasis. Conclusion: An evaluation of short duration of anemia led to unexpected widely metastasized primary anorectal melanoma. Hence anemia presenting at old age should be evaluated in detail including endoscopy of whole gastro-intestinal tract to rule out malignancy.